Your next move : the leader's guide to navigating major career transitions - Watkins, Michael (Boston, Mass : Harvard Business Press, 2009)
Learn to shine in your roles at work, adapt to new roles and make your next move a successful one
Includes index
BSBA
Keywords: Executives; Career development; Promotions; Leadership; Management